Pengaruh Kecepatan Jaringan terhadap Kinerja Aplikasi Cloud Google Drive Berbasis Web - Widiyanto, Widiyanto; Amir Syamsudin (Journal of Engineering and Applied Technology, 2025)
The development of digitalization has led to the massive use of cloud services such as Google Drive, but its performance is greatly influenced by network speed. In Indonesia, the average internet speed still lags behind other countries in ASEAN, so a quantitative analysis of its impact on application performance is needed. This study aims to measure the relationship between network speed variations and the performance of web-based Google Drive through four indicators: upload time, download time, latency, and throughput. The method used is a quantitative experiment with a between-subjects design, testing five speed levels (5, 10, 25, 50, 100 Mbps) on three file sizes (10 MB, 100 MB, 500 MB), each repeated 30 times in a controlled environment using a network emulator. Data were analyzed using descriptive statistics, one-way ANOVA, post-hoc Tukey tests, and linear regression. Results showed that network speed significantly influenced all indicators (p < 0.001), with R² values ranging from 0.87 to 0.96. Increasing speed up to 25 Mbps resulted in significant performance improvements, but beyond this point, a diminishing return phenomenon occurred. Practically, each 1 Mbps increase reduced upload time by 0.075 seconds, download time by 0.068 seconds, latency by 0.215 ms, and increased throughput by 0.019 MB/s.